Análise da arrecadação de ICMS a partir do comércio eletrônico sob a perspectiva da EC 87/2015 - Sá, Danielle Kubrusly de Miranda (2017)
This dissertation proposed to investigate the effect of EC 87/2015 on the collection of ICMS in electronic commerce in the State of Ceará. To fulfill the determined purpose the analysis was decomposed into three dimensions. Initially, an analysis of Internet access and credit was carried out during the period 2002-2016. In the second phase, based on SEFAZ / CE secondary data, we identified the main States of Origin that transact goods with final non-taxpayers resident in Ceará. The third stage made use of time series techniques to identify possible regime changes in the collection and to make monthly forecasts of tax collection related to e-commerce for the period from August 2017 to December 2018. It was found that EC 87 / 2015 promoted the redistribution of tax revenues from the states of the South and Southeast towards Ceará and that the gradual change in the rate differential has promoted persistent increases in the state revenue.